Igneous structure and texture of the ~1.3 Ga Hosenbein anorthosite pluton (Nain, Labrador) and implications for the crystallization of massif-type anorthosite - Voordouw, Ronald (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2010)
ABSTRACT The ca. 1315 Ma Hosenbein massif-type anorthosite pluton (Nain, Labrador) shows complete exposure of a vertical section, described here for the first time, comprising a ~2000 m-thick Main Zone bound by a ~200 m-thick Marginal Zone. The pluton as a whole consists mostly of monocumulate leucogabbronorite, leuconorite, and anortho-site (~94 vol% of all rocks) with elevated abundances of gabbronorite–ferrodiorite (~27 vol%) in the Marginal Zone. Parental magma likely comprised a plagioclase-phyric basaltic melt, containing ~15–45 vol% plagioclase phenocrysts. Crystallization of this magma produced predominantly massive adcumulate–mesocumulate with less abundant, but regular, occurrences of (in order of relative abundance) gabbronorite–ferrodiorite segregations, mottled texture, foliation, pyroxenite aggregates, and modal layering. Additional key petrographic and compositional features include high-T deformation microstructures in plagioclase, vertically consistent mineral compositions, and enrichment of Fe-Ti-P-HFSE-REE in ferrodiorite. Parts of the Marginal Zone show gneissic–mylonitic fabrics that developed parallel to magma conduits. Collectively these features suggest that the textural and structural evolution of the pluton was controlled by: (a) emplacement of plagioclase-phyric magma, (b) establishment of vast cumulus crystal frameworks, (c) porous flow of intercumulus melt, (d) compaction, and (e) synplutonic deformation. These interpretations contrast with previous work emphasizing the importance of magmatic flow and crystal settling/flotation.